nab-Paclitaxel-Based Therapy in Underserved Patient Populations: The ABOUND.70+ Study in Elderly Patients With Advanced NSCLC - Langer, Corey J.; Kim, Edward S.; Anderson, Eric C.; Jotte, Robert M.; Modiano, Manuel; Haggstrom, Daniel E.; Socoteanu, Matei P.; Smith, David A.; Dakhil, Christopher; Konduri, Kartik; Berry, Tymara; Ong, Teng J.; et al. (Frontiers in Oncology, 2018)
The phase 4 ABOUND.70+ trial assessed the safety and efficacy of nab-paclitaxel/carboplatin continuously or with a 1-week break between cycles in elderly patients with advanced non-small cell lung cancer (NSCLC). Patients ≥ 70 years with locally advanced/metastatic NSCLC were randomized 1:1 to first-line nab-paclitaxel days 1, 8, 15 plus carboplatin day 1 of a 21-day cycle (21d) or the same nab-paclitaxel/carboplatin regimen with a 1-week break between cycles (21d+break; 28d). The primary endpoint was the percentage of patients with grade ≥ 2 peripheral neuropathy (PN) or grade ≥ 3 myelosuppression. Other key endpoints included progression-free survival (PFS), overall survival (OS), and overall response rate (ORR). A total of 143 patients were randomized (71 to 21d, 72 to 21d+break). The percentage of patients with grade ≥ 2 PN or grade ≥ 3 myelosuppression was similar between the 21d and 21d+break arms (76.5% and 77.1%; P = 0.9258). Treatment exposure was lower in the 21d arm compared with the 21d+break arm. Median OS was 15.2 and 16.2 months (HR 0.72, 95% CI 0.44–1.19; P = 0.1966), median PFS was 3.6 and 7.0 months (HR 0.48, 95% CI 0.30–0.76; P < 0.0019), and ORR was 23.9% and 40.3% (RR 1.68, 95% CI 1.02–2.78; P = 0.0376) in the 21d and 21d+break arms, respectively. In summary, the 1-week break between treatment cycles significantly improved PFS and ORR, but did not significantly reduce the percentage of grade ≥ 2 PN or grade ≥ 3 myelosuppression. Overall, the findings support the results of prior subset analyses on the safety and efficacy of first-line nab-paclitaxel/carboplatin in elderly patients with advanced NSCLC.